2017
DOI: 10.1021/acs.jmedchem.7b01223
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of a Dual TTK Protein Kinase/CDC2-Like Kinase (CLK2) Inhibitor for the Treatment of Triple Negative Breast Cancer Initiated from a Phenotypic Screen

Abstract: Triple negative breast cancer (TNBC) remains a serious unmet medical need with discouragingly high relapse rates. We report here the synthesis and structure-activity relationship (SAR) of a novel series of 2,4,5-trisubstituted-7H-pyrrolo[2,3-d]pyrimidines with potent activity against TNBC tumor cell lines. These compounds were discovered from a TNBC phenotypic screen and possess a unique dual inhibition profile targeting TTK (mitotic exit) and CLK2 (mRNA splicing). Design and optimization, driven with a TNBC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…At present, many studies have found that high expression of dual specificity protein kinase (TTK), encoded by the TTK gene, is associated with the oncogenesis, progression and treatment resistance of breast cancer (especially TNBC) (Riggs et al, 2017). It was reported that TTK could regulate the growth and epithelial-to-mesenchymal transition of TNBC cells through TGF-β and KLF5 signal pathways, thereby affecting the invasion and metastasis of tumors (King et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies have found that high expression of dual specificity protein kinase (TTK), encoded by the TTK gene, is associated with the oncogenesis, progression and treatment resistance of breast cancer (especially TNBC) (Riggs et al, 2017). It was reported that TTK could regulate the growth and epithelial-to-mesenchymal transition of TNBC cells through TGF-β and KLF5 signal pathways, thereby affecting the invasion and metastasis of tumors (King et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TTK, a genome-surveillance mechanism that is important for cell survival, and has emerged as a candidate target for anticancer therapy (Mason et al 2017 ). Inhibition of TTK has emerged as a promising therapeutic strategy for the treatment of aneuploid tumors, with triple-negative breast cancer (TNBC) (Maia et al 2015 ; Riggs et al 2017 ; Thu et al 2018 ; Zhu et al 2018 ) and malignant mesothelioma (Szymiczek et al 2017 ) important focus of clinical development. Human cancer cells treated with Mps1 inhibitor exhibit effects consistent with Mps1 kinase inhibition, specifically spindle assembly checkpoint inactivation, leading to chromosome missegregation, aneuploidy, and ultimately cell death (Mason et al 2017 ).…”
Section: The Progress Of Ttk In Immunotherapy Of Esophageal Cancermentioning
confidence: 99%
“…CC-671, a potent and selective inhibitor of both monopolar spindle 1 kinase, also known as TTK, and CDC like kinase 2 (CLK2), showed significant anticancer effect in a large panel of cancer cell lines. 32 The anticancer activity of CC-671 is mainly attributed to TTK inhibition. In addition, CLK2 was shown to act as an oncogene in breast cancer and inhibition of CLK2 can lead to apoptosis induction.…”
Section: Introductionmentioning
confidence: 99%